12th ACM Conference on Web Science 2020
DOI: 10.1145/3394231.3397894
|View full text |Cite
|
Sign up to set email alerts
|

Roots of Trumpism: Homophily and Social Feedback in Donald Trump Support on Reddit

Abstract: We study the emergence of support for Donald Trump in Reddit's political discussion. With almost 800k subscribers, "r/The_Donald" is one of the largest communities on Reddit, and one of the main hubs for Trump supporters. It was created in 2015, shortly after Donald Trump began his presidential campaign. By using only data from 2012, we predict the likelihood of being a supporter of Donald Trump in 2016, the year of the last US presidential elections. To characterize the behavior of Trump supporters, we draw f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Participation in this subreddit is a valid proxy to study Donald Trump support, as the rules of this subreddit explicitly state that the community is for "Trump Supporters Only", and that dissenting users will be removed. As such, it has been previously used in literature to analyze the behavior of Trump supporters 34,35 . r/hilla rycli nton and r/Hilla ryFor Ameri ca are the main communities that supported the Hillary Clinton's campaign in 2016.…”
Section: Political Leaning Of Reddit Usersmentioning
confidence: 99%
“…Participation in this subreddit is a valid proxy to study Donald Trump support, as the rules of this subreddit explicitly state that the community is for "Trump Supporters Only", and that dissenting users will be removed. As such, it has been previously used in literature to analyze the behavior of Trump supporters 34,35 . r/hilla rycli nton and r/Hilla ryFor Ameri ca are the main communities that supported the Hillary Clinton's campaign in 2016.…”
Section: Political Leaning Of Reddit Usersmentioning
confidence: 99%
“…The right-leaning community of Donald Trump supporters of r/The_Donald was repeatedly denounced for toxicity, trolling, and harassment [25,33,43,45]. As a result of such misbehavior, it faced a sequence of increasingly restrictive moderation interventions by Reddit administrators:…”
Section: Moderating R/the_donaldmentioning
confidence: 99%
“…Further, self posts tend to be more regulated by forum moderators, suggesting that they are more likely to reflect the norms of the community. r/The_Donald and its role in alt-right politics (Massachs et al, 2020;Ribeiro et al, 2020;Shepherd, 2020), as well as conspiracy theorists on the platform (Klein et al, 2019;Phadke et al, 2021;Samory and Mitra, 2018). Research has indicated a sizable and statistically significant overlap in users between the two subreddits (Massachs et al, 2020;Nithyanand et al, 2017).…”
Section: Wmd and Interpretabilitymentioning
confidence: 99%
“…r/The_Donald and its role in alt-right politics (Massachs et al, 2020;Ribeiro et al, 2020;Shepherd, 2020), as well as conspiracy theorists on the platform (Klein et al, 2019;Phadke et al, 2021;Samory and Mitra, 2018). Research has indicated a sizable and statistically significant overlap in users between the two subreddits (Massachs et al, 2020;Nithyanand et al, 2017). However, these observations have been largely based on subreddit cosubscriber networks, and have paid comparatively less attention to large-scale linguistic patterns over time, a gap to which we hope to contribute.…”
Section: Wmd and Interpretabilitymentioning
confidence: 99%